2020
DOI: 10.1038/s41598-020-69021-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D protects against immobilization-induced muscle atrophy via neural crest-derived cells in mice

Abstract: Vitamin D deficiency is a recognized risk factor for sarcopenia development, but mechanisms underlying this outcome are unclear. Here, we show that low vitamin D status worsens immobilization-induced muscle atrophy in mice. Mice globally lacking vitamin D receptor (VDR) exhibited more severe muscle atrophy following limb immobilization than controls. Moreover, immobilization-induced muscle atrophy was worse in neural crest-specific than in skeletal muscle-specific VDR-deficient mice. Tnfα … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 70 publications
(73 reference statements)
0
21
0
Order By: Relevance
“…In animal studies ( Table 2 ), VitD deficiency has led to detrimental effects in skeletal muscle, mainly resulting in muscle atrophy [ 43 , 44 , 48 ]. Nakamura et al have demonstrated that low VitD status resulted in worse mobilization and induced muscle atrophy in mice [ 44 ] ( Table 2 ). The last authors have concluded that maintaining sufficient levels of VitD is likely to prevent deterioration and skeletal muscle atrophy [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal studies ( Table 2 ), VitD deficiency has led to detrimental effects in skeletal muscle, mainly resulting in muscle atrophy [ 43 , 44 , 48 ]. Nakamura et al have demonstrated that low VitD status resulted in worse mobilization and induced muscle atrophy in mice [ 44 ] ( Table 2 ). The last authors have concluded that maintaining sufficient levels of VitD is likely to prevent deterioration and skeletal muscle atrophy [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nakamura et al have demonstrated that low VitD status resulted in worse mobilization and induced muscle atrophy in mice [ 44 ] ( Table 2 ). The last authors have concluded that maintaining sufficient levels of VitD is likely to prevent deterioration and skeletal muscle atrophy [ 44 ]. In accordance with this study, Gifondorwa et al have reported that a VitD deficient diet resulted in detrimental changes in the structure and function of the neuromuscular junction [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies even used fixation combined with hindlimb unloading to exaggerate the muscle loss induced by no load to build a mouse model of sarcopenia 124 . The immobilization time ranged from 1 to 3 weeks, depending on the researchers' experimental design 120,122–124 . Compared with traditional plaster fixation, surgical staplers and other immobilization models are simple and can be carried out in a few seconds, which makes it possible to carry out high‐throughput analysis with high reproducibility.…”
Section: Classification Of Mouse Models Of Sarcopeniamentioning
confidence: 99%
“…Vitamin D deficiency is common phenomenon in CKD patients. It is reported that maintaining appropriate vitamin D levels is crucial to protect muscle from significant atrophy [ 70 ]. Moreover, iron deficiency in skeletal muscle metabolism is strongly associated with lower exercise tolerance independent from anemia, since it is an essential component of oxygen uptake, transport, storage, erythropoiesis, the mitochondrial electron transport chain, and antioxidant enzymes [ 71 ].…”
Section: Muscle Energy Metabolism and Nutrientsmentioning
confidence: 99%